The Latin American challenge: social cohesion and democracy - Sorj, Bernardo (SciELO Books - Centro Edelstein, 2008)
Based on the work of twenty renowned experts from the region, this ground-breaking book traces the new face of Latin America using clear, straightfoward language that is accessible to a general audience. The current panorama in the region creates new opportunities and dangers for social cohesion in democracy and a revitalized critical approach is needed to arrive at a global interpretation of the social dynamics in Latin America.